Implementation of Public Service Quality at Morokrembangan Community Health Center, Surabaya City - Mutiara Julianty (International Journal of Social, Economic, and Business, 2025)
This study aims to evaluate the implementation of public healthcare service quality at Puskesmas Morokrembangan, Surabaya, using the SERVQUAL model, which encompasses five key dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The research employs a descriptive quantitative approach with data collected from 100 respondents who had accessed healthcare services at the facility at least twice within the past year. The findings indicate that all service quality dimensions fall within the “good” category, with the empathy dimension receiving the highest average score, particularly in aspects related to respectful and non-discriminatory service. In contrast, the reliability dimension emerged as the area requiring the most attention, especially regarding public perceptions of the alignment between service requirements and the types of services provided. These findings suggest that, although Puskesmas Morokrembangan has succeeded in providing inclusive and human-centered services, improvements are still necessary in enhancing procedural clarity, standardizing service requirements, and leveraging information technology to strengthen service communication. This study contributes to the broader discourse on service quality in public health institutions and offers practical implications for enhancing the delivery of digitally integrated primary healthcare services.